Sequences conserved by selection across mouse and human malaria species - Chuang Jeffrey H (BMC Genomics, 2007)
Abstract Background Little is known, either experimentally or computationally, about the genomic sequence features that regulate malaria genes. A sequence conservation analysis of the malaria species P. falciparum, P. berghei, P. yoelii, and P. chabaudi could significantly advance knowledge of malaria gene regulation. Results We computationally identify intergenic sequences conserved beyond neutral expectations, using a conservation algorithm that accounts for the strong compositional biases in malaria genomes. We first quantify the composition-specific divergence at silent positions in coding sequence. Using this as a background, we examine gene 5' regions, identifying 610 blocks conserved far beyond neutral expectations across the three mouse malariae, and 81 blocks conserved as strongly across all four species (p < 10-6). Detailed analysis of these blocks indicates that only a minor fraction are likely to be previously unknown coding sequences. Analogous noncoding conserved blocks have been shown to regulate adjacent genes in other phylogenies, making the predicted blocks excellent candidates for novel regulatory functions. We also find three potential transcription factor binding motifs which exhibit strong conservation and overrepresentation among the rodent malariae. Conclusion A broader finding of our analysis is that less malaria intergenic sequence has been conserved by selection than in yeast or vertebrate genomes. This supports the hypothesis that transcriptional regulation is simpler in malaria than other eukaryotic species. We have built a public database containing all sequence alignments and functional predictions, and we expect this to be a valuable resource to the malaria research community.